Public health facility quality and child immunization outcomes in rural India: A decomposition analysis. Issue 16 (6th April 2022) - Summan, Amit; Nandi, Arindam; Schueller, Emily; Laxminarayan, Ramanan
Abstract: Universal coverage of routine childhood vaccines remains a challenge in many low- and middle-income countries (LMICs). In India, vaccination campaigns have increased full immunization coverage among 12–23 month old children from an estimated 62% in 2015–2016 to 76% in 2019–2020. Long-term improvements in coverage will likely require systemic changes to both the supply and demand sides of immunization programs. However, the effect of health system inputs on child vaccination outcomes remains poorly quantified in India. We examined the association between the quality of public health facilities and child vaccination outcomes in rural India using data from the nationally representative Integrated Child Health and Immunization Survey (2015–2016) which covered 1, 346 public primary health sub-centers and 44, 571 households. We constructed two indices of sub-center quality using multiple correspondence analysis: one related to the general health infrastructure quality and the other measuring vaccine service delivery. Using probit regression, we analyzed the relationship between vaccination outcomes in children under 2 years of age and sub-center quality, controlling for household socioeconomic characteristics. Additionally, we conducted Fairlie decomposition analysis by wealth group — bottom wealth quintile relative to the top four wealth quintiles— to examine factors contributing to gaps in immunization between rich and poor households. Infrastructure quality index was positively associated with completion of seven vaccination outcomes: full immunization, DPT-1 (first dose of diphtheria, pertussis, and tetanus), DPT-2, DPT-3, Bacillus Calmette–Guérin (BCG), hepatitis B (birth dose), and on-time vaccination (OTV). Vaccine service delivery index was positively associated with completion of measles vaccination. The distribution of infrastructure quality contributed to increased gaps in full immunization and OTV between rich and poor households, while greater proximity to vaccination site for poorer households reduced these gaps. Improved quality of health facilities, particularly facilities used by low-income households, may improve vaccination outcomes.